Twenty-four-hour pH monitoring of gastric conduit in post-esophagectomy patients: correlation with clinical and endoscopic parameters in a prospective cohort study from India - Jain, Vishu; Varshney, Vaibhav Kumar; Soni, Subhash Chandra; Selvakumar, B; Varshney, Peeyush; Agarwal, Lokesh; Agarwal, Ashish; Birda, Chhagan Lal (Journal of minimally invasive surgery, 2025)
Esophagectomy for malignancy leads to decreased gastric conduit acidity due to bilateral vagotomy and fundic gland area reduction. However, reflux symptoms occur. The changes in pH of gastric conduit and esophageal remnant post-esophagectomy were studied and correlated clinically, endoscopically and with positivity. We studied 20 patients prospectively undergoing esophagectomy for malignancy from January 2022 to December 2023. The patients underwent pre- and postoperative clinical assessment, 24-hour pH monitoring, and esophagoduodenoscopy with testing and analysis. Postoperatively, the total percent (%) time pH <4 was nonsignificantly increased to 17.95% ( = 0.754) in the esophageal remnant and significantly decreased to 53.5% ( = 0.012) in the stomach. Postoperatively, the -positive patients had a non-significantly higher total % time pH <4 in the esophageal remnant than -negative patients (29.47 ± 33.54 vs. 6.44 ± 11.58, = 0.064) and slightly lower total % time pH <4 in the stomach (53.30 ± 46.08 vs. 53.71 ± 31.20, = 0.982). The total % time pH <4 in the gastric conduit was significantly correlated with the esophageal remnant ( = 0.002), showing a correlation coefficient of 0.629. There is a significant increase in gastric conduit pH post-esophagectomy with increased exposure to the esophageal remnant mucosa proportional to gastric acidity. infection does not affect gastric aciditiy and acid reflux after esophagectomy.